DESKRIPSI PEMAHAMAN PESERTA DIDIK TERHADAP BARISAN ARITMATIKA DIKAITKAN DENGAN SURAH AL-KAHF AYAT 22 - Sulala, Anis; Rustam, Rustam; BS, Dian Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This research seeks to explore students"™ comprehension of the concept of arithmetic sequences in relation to Surah Al-Kahf verse 22 at MTs Al-Ihsan Pontianak. This topic was chosen because many students still struggle to master arithmetic sequence material, particularly in determining the value of then term and the sum of all terms up to n. The study employed a descriptive qualitative method using specific data gathering techniques consisting of open-ended tests and semistructured interviews. The research subjects were eighth-grade students who had already studied arithmetic sequences. The research instruments were developed based on indicators of mathematical understanding and modified to integrate the concept of arithmetic sequences with Islamic values found in Surah Al-Kahf verse 22. It was found that 29% of participants demonstrated well-developed understanding, 59% moderate, also 12% low. The main difficulties included applying formulas, identifying patterns, and making deep connections between the mathematical concepts and the Qur"™anic verse. However, some students were able to recognize the number pattern in the verse (3, 5, 7) as an arithmetic sequence with a constant difference. These findings indicate that integrating Qur"™anic verses into mathematics instruction has the potential to enhance students"™ understanding, both cognitively and spiritually. The study recommends the development of contextual and religious learning models to strengthen the connection between mathematical concepts and Islamic values.